PERGULATAN PEMIKIRAN ISLAM DI RUANG PUBLIK MAYA (ANALISIS TERHADAP TIGA WEBSITE ORGANISASI ISLAM DI INDONESIA) - Mustaqim, Muhamad (LP2M IAIN kUDUS, 2013)
THE ISLAMIC THINKING IN THE CYBERSPACE (AN ANALYSIS OF THREE WEBSITE ISLAMIC ORGANIZATIONS IN INDONESIA). The shift from physical public space in the virtual public space becomes a contestation for social organizations, including Islamic organizations. This paper intends to analyze the tendency of the struggle of Islamic thought to public spaces through official website of each organization Islam. As a representation of Islamic organizations, this study selected three Islamic organizations representing certain trends and typologies. Namely, Hizb ut-Tahrir Indonesia (HTI) representing transnational fundamentalist group, the Liberal Islam Network (JIL), which is a representation of the liberal group, and the Nahdlatul Ulama (NU), which represents the middle and moderate currents. This paper examines the trends and the existing contents of the three websites, does not highlight a deeper understanding of religious activity in the area of empirical Islamic organizations.keywords: Public Space, Website, the Islamic Organization.Pergeseran dari ruang publik yang bersifat fisik pada ruang publik maya menjadi kontestasi bagi organisasi-organisasi sosial, termasuk di dalamnya organisasi Islam. Tulisan ini bermaksud menganalisis kecenderungan pergulatan pemikiran Islam pada ruang publik maya melalui website resmi masing-masing organisasi Islam. Sebagai representasi dari organisasi-organisasi Islam, dalam kajian ini dipilih tiga organisasi Islam yang mewakili kecenderungan dan tipologi tertentu. Yaitu, Hizbut Tahrir Indonesia (HTI) yang mewakili kelompok fundamentalis-transnasional, Jaringan Islam Liberal (JIL) yang merupakan representasi dari kelompok liberal, dan Nahdlatul Ulama (NU) yang mewakili arus tengah dan moderat. Tulisan ini hanya mengkaji kecenderungan dan konten yang ada dalam tiga website tersebut, tidak menyoroti lebih mendalam tentang aktivitas keberagamaan organisasi Islam di wilayah empiris.kata kunci: Ruang Publik, Website, Organisasi Islam.